Low complexity cooperative multicast beamforming in multiuser multicell downlink networks - Dartmann, G.; Xitao Gong; Ascheid, G. (2011 6th International ICST Conference on Cognitive Radio Oriented Wireless Networks and Communications (CROWNCOM), 2011)
This paper presents a low complexity sub-optimal algorithm for the max-min beamforming problem in multicell multicast transmission. The beam pattern is jointly optimized for all users inside a cell in a multicell scenario such that the signal to interference plus noise ratio (SINR) of the worst users is maximized subject to a limited sum power. The presented algorithm is based on the Lagrangian dual problem of the downlink max-min beamforming problem. The SINR of the presented algorithm is very close to the SINR of the known solution based on the more complex semidefinite programming.